Exploring the Cultural Values of Naming La Ode and Wa Ode in Muna and Buton Communities of South East Sulawesi - Jalil, Abdul; Hasniah; Ashmarita (TALENTA Publisher, 2021)
This theme was inspired by the RRI Kendari program at the event of networking culture organized by the Regional Office of Sulawesi on May 15, 2017. La Ode and Wa Ode were noble titles or at least considered the prayers from parents to their children so that their children would become leaders or nobles in the future. In addition, La Ode and Wa Ode were the acronyms of the two statements of the Islamic creed. The word